SPECIFICS OF MANAGING THE CREATIVITY OF HOTEL AND RESTAURANT ENTERPRISES PERSONNEL – A DIRECTION FOR INCREASING COMPETITIVENESS (INNOVATIVE ECONOMY, 2026)
Kondratska L.P. SPECIFICS OF MANAGING THE CREATIVITY OF HOTEL AND RESTAURANT ENTERPRISES PERSONNEL – A DIRECTION FOR INCREASING COMPETITIVENESSPurpose. The aim of the article is to substantiate the specifics of managing the creativity of hotel and restaurant personnel as a tool for strengthening its competitiveness and to identify key management approaches and practical mechanisms capable of ensuring the systematic reproduction and realization of the creative potential of employees in service activities and innovative development of the enterprise.Methodology of research. A complex of general scientific and special research methods was used in the process of preparing the article. Theoretical generalization of scientific approaches to the interpretation of personnel creativity, creative management and the role of the creative potential of employees in the hospitality sector was carried out using the methods of analysis and synthesis, induction and deduction, comparison, systemic, structural and functional approaches. The method of logical generalization, cause-and-effect analysis and graphic modeling was used to identify the key components of employee creativity, substantiate the conditions for effective management of personnel creativity and determine its impact on the competitiveness of a hotel and restaurant enterprise.Findings. It is substantiated that in conditions of high dynamics of consumer expectations, increased competition and the intangible nature of the service product, personnel creativity turns into a strategic resource for increasing the competitiveness of a hotel and restaurant enterprise. Scientific approaches to the interpretation of staff creativity are summarized and it is proven that its applied content in the field of hospitality is manifested in the ability of employees to produce original and at the same time useful solutions for improving service, updating the product, optimizing business processes, forming a recognizable atmosphere of the establishment and flexibly responding to non-standard requests of guests. It is substantiated that the effectiveness of employees' creative activity is ensured by the interaction of three basic components - professional expertise, creative thinking skills and motivation, and it is internal motivation that is a key prerequisite for sustainable creative manifestations in service situations. The key conditions for successful management of staff creativity in the hotel and restaurant sector are determined and it is proven that their coordinated functioning ensures an increase in the quality of customer experience, the formation of a unique value proposition, the innovation of business processes, brand strengthening, increased customer loyalty, repeat visits and financial results of the enterprise. A process approach to managing personnel creativity is proposed in the form of sequential stages - from diagnosing creative potential and forming a creative environment to implementing solutions, evaluating results and adjusting management influences.Originality. The theoretical and applied approach to researching the creativity of hotel and restaurant personnel as a managed factor of competitive development has been further developed, which, unlike existing approaches, combines the competence, motivational and organizational and process components in a single management logic. The understanding of the specifics of managing personnel creativity in the hospitality sector has been improved by substantiating the connection between professional expertise, creative and critical thinking, internal motivation of employees and the achievement of measurable competitive effects. The proposed process approach allows us to consider the creativity of personnel not as a situational characteristic or a separate form of initiative, but as a systemic management object integrated into the personnel policy, organizational culture, motivational mechanisms and management system of a hotel and restaurant enterprise.Practical value. The research results can be used by managers and leaders of hotel and restaurant enterprises in the process of forming personnel policy, building a creative environment, improving personnel motivation systems, organizing professional development of employees and implementing service innovations. Some provisions of the article can be applied to develop programs to stimulate creative behavior of personnel, implementing mechanisms for generating and selecting ideas, assessing the contribution of employees to the development of service and increasing the competitiveness of the institution. The practical use of the proposed approach will contribute to improving the quality of customer experience, strengthening the brand, improving reputation indicators, increasing guest loyalty and increasing the economic performance of the hotel and restaurant enterprise.Key words: staff creativity, creative management, hotel and restaurant enterprise, creative environment, motivation, customer experience, service innovations, competitiveness.
Keywords: creative management; staff creativity; hotel and restaurant enterprise; creative environment; motivation; customer experience; service innovations; competitiveness